Identification of a genotoxic mechanism for 2-nitroanisole carcinogenicity and of its carcinogenic potential for humans - Stiborová, Marie; Miksanová, Markéta; Smrcek, Stanislav; Bieler, Christian A; Breuer, Andrea; Klokow, Karl A; Schmeiser, Heinz H; Frei, Eva (Carcinogenesis, 2004)
2-Nitroanisole (2-NA) is an important industrial pollutant and a potent bladder carcinogen for rodents. The mechanism of its carcinogenicity was investigated in this study. Here we have used two independent methods, (32)P-post-labeling and (3)H-labeled 2-NA, to show that 2-NA binds covalently to DNA in vitro after reductive activation by human hepatic cytosol and xanthine oxidase (XO). We also investigated the capacity of 2-NA to form DNA adducts in vivo. Male Wistar rats were treated i.p. with 2-NA (0.15 mg/kg body wt daily for 5 days) and DNA from several organs was analyzed by (32)P-post-labeling. Two 2-NA-specific DNA adducts, identical to those found in DNA incubated with 2-NA and human hepatic cytosol or XO in vitro, were detected in the urinary bladder (3.4 adducts/10(7) nt), the target organ, and, to a lesser extent, in liver, kidney and spleen. The two DNA adducts found in rat tissues in vivo were identified as deoxyguanosine adducts derived from a 2-NA reductive metabolite, N-(2-methoxyphenyl)hydroxylamine. This reactive metabolite of 2-NA was identified in incubations with human hepatic cytosol, besides 2-methoxyaniline (o-anisidine). The results of our study, the first report on the potential of human cytosolic enzymes to contribute to the activation of 2-NA by nitroreduction, strongly suggest a carcinogenic potency of this rodent carcinogen for humans.
Keywords: senioři; karcinogeny; Liver; Rats; játra; xanthinoxidasa; DNA; mladiství; DNA Adducts; Middle Aged; NAD(P)H Dehydrogenase (Quinone); Rats, Wistar; mužské pohlaví; Urinary Bladder; NAD(P)H dehydrogenasa (chinon); Adult; močový měchýř; aniliny; dítě; krysa rodu Rattus; slezina; Child; Xanthine Oxidase; Aldehyde Oxidase; Child, Preschool; Cytosol; ženské pohlaví; aldehydoxidasa; zvířata; Humans; předškolní dítě; cytosol; anisoly; Aniline Compounds; Carcinogens; Phosphorus Isotopes; ledviny; lidé středního věku; izotopy fosforu; potkani Wistar; dospělí; Kidney; Female; adukty DNA; Aged; Anisoles; Adolescent; Spleen; lidé; Male; Animals